Abiotic stress as a dynamic strategy for enhancing high value phytochemicals in microalgae: Critical insights, challenges and future prospects - Suparmaniam, Uganeeswary; Lam, Man Kee; Lim, Jun Wei; Tan, Inn Shi; Chin, Bridgid; Shuit, Siew Hoong; Lim, Steven; Pan, Yean Ling; Kiew, Peck Loo (2023)
Microalgae showcase an extraordinary capacity for synthesizing high-value phytochemicals (HVPCs), offering substantial potential for diverse applications across various industries. Emerging research suggests that subjecting microalgae to abiotic stress during cultivation and the harvesting stages can further enhance the accumulation of valuable metabolites within their cells, including carotenoids, antioxidants, and vitamins. This study delves into the pivotal impacts of manipulating abiotic stress on microalgae yields, with a particular focus on biomass and selected HVPCs that have received limited attention in the existing literature. Moreover, approaches to utilising abiotic stress to increase HVPCs production while minimising adverse effects on biomass productivity were discussed. The present study also encompasses a techno-economic assessment (TEA) aimed at pinpointing significant bottlenecks in the conversion of microalgae biomass into high-value products and evaluating the desirability of various conversion pathways. The TEA methodology serves as a valuable tool for both researchers and practitioners in the quest to identify sustainable strategies for transforming microalgae biomass into high-value products and goods. Overall, this comprehensive review sheds light on the pivotal role of abiotic stress in microalgae cultivation, promising insights that could lead to more efficient and sustainable approaches for HVPCs production.